308 nm Excimer laser combined with 0.1% tacrolimus ointment for treatment of localized vitiligo - Kabir, Ahmed Raihan; Jing, Hai Xia (International Journal of Research in Dermatology, 2021)
Background: Vitiligo is a long-term skin disease identified by spots of the skin missing their pigment. The spots of skin changed turn white and usually have distinctive perimeters. The hairs that exist on the skin may also turn white due to this disease. Patients inside of the mouth and nose may also be affected by vitiligo. The objective of the study was to analyze results of using 308 nm excimer laser combined with tacrolimus 0.1% ointment for treating the patients associated with localized vitiligo. Methods: This research adopted a mixed method consisting a qualitative approach, a survey of related articles from renowned journals. Regarding data collected from patient’s database who underwent treatment at BSMMU, Bangladesh. Patients are divided into 3 groups. The first group included 30 vitiligo patients treated with topical 0.1% tacrolimus ointment applied twice daily for 10 weeks of follow-up. The second group consists of 30 vitiligo patients treated with 308 nm excimer laser applied three times a week for 10 weeks of follow-up. The third group of 30 vitiligo patients treated with 308 nm excimer laser combined tacrolimus 0.1% ointment applied twice daily for tacrolimus and three time a week for 308 nm excimer laser for 10 weeks). Results: The research result showed that the combined treatment of 308 nm excimer laser with 0.1% tacrolimus ointment and 308 nm excimer laser monotherapy are effective, reliable and well tolerated for the vitiligo treatment. Conclusions: The research result confirms the efficacy of excimer laser therapy in vitiligo patients, suggesting that an association with 0.1% tacrolimus may represent an advance in the treatment of the disease.